Gaucher’s disease and retinitis pigmentosa : A case report - Nadir KAYA; Mustafa KETENCİ and Arif KOŞAR and Nurşen ARITÜRK and İlkser AKPOLAT and Levent ALTINTOP and Hakkı KAHRAMAN (Turkish Journal of Gastroenterology, 2019)
-